The Stochastics of Threshold Accepting: Analysis of an Application to the Uniform Design Problem - Peter Winker (Universität Erfurt, Staatswissenschaftliche Fakultät, 2005)
Threshold Accepting (TA) is a powerful optimization heuristic from the class of stochastic local search algorithms. It has been applied successfully to different optimization problems in statistics and econometrics, including the uniform design problem. Using the latter application as example, the stochastic properties of a TA implementation are analyzed. We provide a formal framework for the analysis of optimization heuristics like TA, which can be used to estimate lower bounds and to derive convergence results. It is also helpful for tuning real applications. Based on this framework, empirical results are presented for the uniform design problem. In particular, for two problem instances, the rate of convergence of the algorithm is estimated to be of the order of a power of -0.3 to -0.7 of the number of iterations.
Keywords: 330; Heuristic optimization; Threshold Accepting; Stochastic analysis of heuristics; Mathematische Optimierung; Stochastischer Prozess; Heuristisches Verfahren; Theorie; uniform design problem